Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.2174/1745017901309010255
|View full text |Cite
|
Sign up to set email alerts
|

In Sickness and in Health: a Literature Review about Function of Social Support within Anxiety and Heart Disease Association

Abstract: A narrative review of the major evidence concerning the relationship between anxiety, social support and cardiac disease was conducted. Literature demonstrates that a strict relationship between anxiety, social support and cardiac disease outcomes subsists. However, the function of social support within anxiety and heart disease association remains unclear and needs to further researches to be established. Moreover evidence suggests that it’s the quality of close relationships to play an important role in affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 106 publications
(94 reference statements)
1
4
0
Order By: Relevance
“…In line with previous fi ndings conducted in Cardiac Rehabilitation, our results showed that the presence of children could be considered as a predictor of depression, specifi cally patients without children were more depressed than patients with children [42,43]. This result underlines the role of children as crucial to social support, in predicting less emotional distress and contributing to emotional health, so to a greater support given by family members and children becomes lower levels of depression [44].…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous fi ndings conducted in Cardiac Rehabilitation, our results showed that the presence of children could be considered as a predictor of depression, specifi cally patients without children were more depressed than patients with children [42,43]. This result underlines the role of children as crucial to social support, in predicting less emotional distress and contributing to emotional health, so to a greater support given by family members and children becomes lower levels of depression [44].…”
Section: Discussionsupporting
confidence: 91%
“…Poor social support among patients with ACS was observed in secondary analyses of a randomized trial to reduce the effectiveness of treatment with antidepressants [59]. The quality of social support plays an important role, as overprotective behaviors of partners can have an adverse effect [58]. Interestingly, in the current study marital status and social support were associated with presence of depressive symptoms independently and in opposite directions.…”
Section: Discussionmentioning
confidence: 64%
“…In studies on breast cancer [53], promotion of physical activity may have the additional benefit of improving self-esteem, a factor associated with depression and anxiety in this study and a predictor of mortality in the general population [54]. In addition, according to previous studies [43, 5558], the inverse association between high social support and low levels of anxiety and depression points to another important target for prevention as it is supported by firm evidence from previous studies. Poor social support among patients with ACS was observed in secondary analyses of a randomized trial to reduce the effectiveness of treatment with antidepressants [59].…”
Section: Discussionmentioning
confidence: 66%
“…Except paranoid ideation and psychoticism dimensions, mean scores of rest dimensions including somatization, obsession-compulsion, interpersonal sensitivity, depression, anxiety, hostility, and phobic anxiety in the stroke group were significantly higher than those in the control group. Various studies have established the association between social support and health [23] . Social support plays an important role in coping mechanism to deal with stress and psychological or physical symptoms, and has been recognized as a salient construct in nursing research.…”
Section: Discussionmentioning
confidence: 99%